Low dimensional titanium dioxide nanowires synthesized by hydrothermal autoclave method/ Asiah Mohd Nor - Mohd Nor, Asiah (2020)
Titanium dioxide, TiO2 nanowires are an emerging class of TiO2 nanostructures. Hydrothermal is the selected method in this study because of its simplicity and works relatively at low temperatures, which has the advantage of easy control over the synthesis process. Synthesizing TiO2 nanowires using alkaline hydrothermal method required a very long reaction time which is more than 20 hours. Therefore, it is important to produce TiO2 nanowires in a short time and the effect of several processing parameters such as hydrothermal growth time, hydrothermal growth temperature, solvent concentration, precursor concentration, filling fraction and annealing temperature on the morphology and structural properties of low dimensional TiO2 nanowires were systematically investigated. X-ray diffraction (XRD) pattern showed that the produced nanowires showed high crystallinity and mainly in the anatase phase TiO2. Raman spectroscopy of TiO2 nano wires supported the results of XRD analysis, i.e., the predominance of the anatase phase TiO2. The shorter growth time of 6 hour is a novel finding in this study. From FESEM images, it was suggested that the starting material which is TiO2 nano particle rearranged itself into an elongated structure as it received sufficient amount of energy within the reaction time as low as 3 h to completely transform into nano wires product and this result is also support the explanation that TiO2 nanowires are directly formed during the hydrothermal process. The morphology and structural properties of hydro thermally synthesized TiO2 nanowires are temperature-dependent. It was found that suitable synthesis temperature is 150°C. Results from XRD and Raman spectra revealed that the structural properties of nanowires are significantly affected by the percentage of filling fraction of solution in autoclave, the concentration of precursor solution and the concentration of solvent. The effect of annealing temperature from 400°C to 900°C was investigated. From FESEM observation, it was discovered that the TiO2 nano wires maintain its structure up to 500°C, while annealing at 600°C resulted in the breakage of nano wires into smaller particles, consequently underwent further transformation from the anatase to the rutile phase with simultaneous re crystallization to rod-like structures at temperature of 900°C and this was revealed by XRD results. The silicon doped TiO2 (TiO2: Si) nano wires have been successfully synthesized and the effect of silicon content (wt%) on the morphology, structural and optical band gap were investigated. The silicon do pant promoted the formation of rutile phase rather than anatase phase TiO2 as shown by XRD pattern and revealed by Raman spectroscopy. The silicon doped TiO2 (TiO2: Si) nano wires has optical band gap of ~3.00 eV compared to TiO2 nano wires which exhibited band gap of 3.28 eV.